Friday

April 18, 2014

April 18, 2014

Posted by **carla** on Saturday, July 14, 2007 at 7:12am.

n^2+(n+1)^2+2n = 85

n^2+n^2+2n+1=85

2n^2+2n=84

n^2+n=42

n^2+n-42=0

(n-6)(n+7)=0

n=6

n=-7

Is my work and answer correct?

-7 is not a positive integer. Your first equation is wrong, because the 2n term should not be there. Your second equation is correct, and after that you correectly solve for n. Since they ask for postive integer solutions only, the only number that fits, for n, is 6. The second integer will by definition be n+1, which is 7.

**Related Questions**

bobpursley, math,correction - Let n be a postive integer, then n+1 is the next ...

algebra - So... I know the answer to the question because it's something we ...

math, algebra - 2a+2ab+2b I need a lot of help in this one. it says find two ...

Algebra - Hello, I have been trying a few ways to do this problem and am not ...

Abstract Algebra - If 2^n>n^2 and n>5, then 2^n+1>(n+1)^2 Proof: ...

Pre-cal - use mathematical induction to prove that 1^2 + 2^2 + 3^2 + ... + n^2...

Algebra - Find two consecutive positive integers such that the sum of the square...

Algebra - The sum of two consecutive odd integers is 24. Which equation can be ...

math - The sum of squares formula is given by 1^2+2^2+3^2+…+n^2=n(n+1)(2n+1)/6. ...

math - Hi. I'm having trouble with the summation of n from i=2 of ((2^n-i)(2^n...